A quick fault location and isolation method for distribution network based on adaptive reclosing. Issue 4 (18th October 2021) - Zhang, Wei; Chang, Zhongxue; Zhang, Chenhao; Song, Guobing; Tan, Weibin
Abstract: Feeder automation is important to improve the reliability of power supply for distribution network. Existing voltage‐time feeder automation scheme exists the problems of long fault processing time and the upstream switches of the fault point need to tolerate fault current twice and the upstream sections need to experience two short time power outage. In this paper, a quick fault location and isolation method for distribution network based on adaptive reclosing is proposed. Three key technologies of the strategy are introduced, including a phase segregated switch of the distribution network based on the permanent magnet operating structure, the phase selector based on transient current characteristics, and the temporary fault and permanent fault identification method based on the power frequency voltage characteristics. The proposed strategy can avoid the second impact on upstream switches and power‐off of the upstream section in case of the permanent fault and can effectively shorten the fault processing time.